Phytochemicals for the Management of Melanoma - Chandra Pal, Harish; Marchiony Hunt, Katherine; Diamond, Ariana; A. Elmets, Craig; Afaq, Farrukh (Mini Reviews in Medicinal Chemistry, 2016)
Melanoma claims approximately 80% of skin cancer-related deaths. Its life-threatening nature is primarily due to a propensity to metastasize. The prognosis for melanoma patients with distal metastasis is bleak, with median survival of six months even with the latest available treatments. The most commonly mutated oncogenes in melanoma are BRAF and NRAS accounting approximately 60% and 20% of cases, respectively. In malignant melanoma, accumulating evidence suggests that multiple signaling pathways are constitutively activated and play an important role in cell proliferation, cell survival, epithelial to mesenchymal transition, metastasis and resistance to therapeutic regimens. Phytochemicals are gaining considerable attention because of their low toxicity, low cost, and public acceptance as dietary supplements. Cell culture and animals studies have elucidated several cellular and molecular mechanisms by which phytochemicals act in the prevention and treatment of metastatic melanoma. Several promising phytochemicals, such as, fisetin, epigallocatechin-3-gallate, resveratrol, curcumin, proanthocyanidins, silymarin, apigenin, capsaicin, genistein, indole-3-carbinol, and luteolin are gaining considerable attention and found in a variety of fresh fruits, vegetables, roots, and herbs. In this review, we will discuss the preventive potential, therapeutic effects, bioavailability and structure activity relationship of these selected phytochemicals for the management of melanoma.
Keywords: Melanoma